2002
DOI: 10.1029/2001jd000934
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of lake ice dynamics and morphology on Lake El'gygytgyn, NE Siberia, using synthetic aperture radar (SAR) and Landsat

Abstract: [1] A time series of more than 450 combined ERS-2, Radarsat-1, and Landsat-7 scenes acquired between 1998 and 2001 was analyzed to develop a fairly complete picture of lake ice dynamics on Lake El'gygytgyn, NE Siberia (67.5°N, 172°E). This 14-km 3 lake partially fills a meteorite impact crater formed 3.6 million years ago and is home to a paleoenvironmental coring project. The duration of lake ice cover and the onset of lake ice breakup are important both to interpretations of the archived sediment core record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
99
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(99 citation statements)
references
References 19 publications
0
99
0
Order By: Relevance
“…The open water season usually starts during the mid of July. A complete lake ice cover does not become formed again until Late October (Nolan et al, 2003).…”
Section: Site Informationmentioning
confidence: 99%
“…The open water season usually starts during the mid of July. A complete lake ice cover does not become formed again until Late October (Nolan et al, 2003).…”
Section: Site Informationmentioning
confidence: 99%
“…The 175 m deep, 12 km wide lake lies inside a 3.6 million year old meteorite impact crater that is 18 km wide and has presumably been filling with sediments since the time of the impact. The impact, the crater, the sediment core, and the physical environment are all well-described in a series of prior papers (Belya and Chershnev, 1993;Glushkova, 1993;Layer, 2000;Nowaczyk et al, 2002;Nolan et al, 2003;Cherapanova et al, 2007;Glushkova and Smirnov, 2007;Melles et al, 2007;Minyuk et al, 2007;Nolan and Brigham-Grette, 2007;Brigham-Grette, 2009;Swann et al, 2010) and those found in this special issue (Melles et al, 2012;Minyuk et al, 2013).…”
Section: Introductionmentioning
confidence: 91%
“…Our prior remote sensing from 1997-2001 indicates that snowmelt on the lake surface begins in mid-May, a moat forms at the edge of the lake ice in the last week of June, and complete ice melt occurs in mid-July. Once the moat opens up in June, the ice pack is subjected to substantially higher mechanical erosion due to wind shove, and our remote sensing data show (Nolan et al, 2003) that soon after moat formation, the ice pack forms major leads across the lake at deltas or outcrops that jut into the lake (e.g., at Stream 12 on the west side, Nolan and Brigham-Grette, 2007). During this time, about half the melt energy is supplied by solar absorption in the ice pack, and crystal grain boundaries weaken, forming candle ice which lacks the cohesion of the winter ice pack (Locke, 1990).…”
Section: Ice Melt Modelingmentioning
confidence: 99%
See 2 more Smart Citations